2022
DOI: 10.1002/ange.202202379
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐Stabilized Silylzinc Pivalates for Nickel‐Catalyzed Carbosilylation of Alkenes

Abstract: We herein report the preparation of solid and salt-stabilized silylzinc pivalates from the corresponding silyllithium reagents via transmetalation with Zn(OPiv) 2 . These resulting organosilylzinc pivalates show enhanced air and moisture stability and unique reactivity in the silylative difunctionalization of alkenes. Thus, a practical chelation-assisted nickel-catalyzed regioselective alkyl and benzylsilylation of alkenes has been developed, which provides an easy method to access alkyl silanes with broad sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Organozinc reagents are satisfying candidates of mild nucleophiles with good functional group compatibility and versatile reactivity in catalytic cross-coupling reactions. Lei et al demonstrated that changing the anions of Ar–ZnX from Cl to Br or I will result in very different kinetics in palladium and nickel catalysis. Very recently, Knochel and us further disclosed the dramatic effects of carboxylate-coordination for improving the stability and reactivity of Ar–Zn and Si–Zn reagents . These unique paradigms of the counterion-effect in organozinc pivalates are novel in 3d transition metal-catalyzed alkene difunctionalizations, allowing us to devise a practical and efficient carbosulfonylation of alkenes using industrial friendly cobalt catalysis. Hence, we envisioned capitalizing on the combination of (a) a practical, robust cobalt catalyst that favors rapid radical addition of alkenes with sulfonyl chlorides, (b) both aryl and alkylzinc pivalates as the nucleophiles that exhibit providential reducibility and transmetalation, and (c) mild reaction conditions at 23 °C to achieve chemo-, regio-, and stereoselective three-component cross-coupling of broad sulfonyl chlorides, alkenes, 1,3-dienes, and organozinc pivalates.…”
mentioning
confidence: 99%
“…Organozinc reagents are satisfying candidates of mild nucleophiles with good functional group compatibility and versatile reactivity in catalytic cross-coupling reactions. Lei et al demonstrated that changing the anions of Ar–ZnX from Cl to Br or I will result in very different kinetics in palladium and nickel catalysis. Very recently, Knochel and us further disclosed the dramatic effects of carboxylate-coordination for improving the stability and reactivity of Ar–Zn and Si–Zn reagents . These unique paradigms of the counterion-effect in organozinc pivalates are novel in 3d transition metal-catalyzed alkene difunctionalizations, allowing us to devise a practical and efficient carbosulfonylation of alkenes using industrial friendly cobalt catalysis. Hence, we envisioned capitalizing on the combination of (a) a practical, robust cobalt catalyst that favors rapid radical addition of alkenes with sulfonyl chlorides, (b) both aryl and alkylzinc pivalates as the nucleophiles that exhibit providential reducibility and transmetalation, and (c) mild reaction conditions at 23 °C to achieve chemo-, regio-, and stereoselective three-component cross-coupling of broad sulfonyl chlorides, alkenes, 1,3-dienes, and organozinc pivalates.…”
mentioning
confidence: 99%